Real-life experience with first generation HCV protease inhibitor therapy in Germany: The prospective, non-interventional PAN cohort - Mauss, S.; Böker, K.; Buggisch, P.; Christensen, S.; Hofmann, W. P.; Schott, E.; Pfeiffer-Vornkahl, H.; Alshuth, U.; Hüppe, D. (Zeitschrift für Gastroenterologie, 2015)
Background and Aims: The efficacy and safety of peginterferon alfa-2a (PEG-IFN) plus ribavirin (RBV) and either boceprevir (BOC) or telaprevir (TVR), and physician adherence to treatment algorithms were evaluated in patients included in an ongoing non-interventional study (PAN) enrolling adults with chronic hepatitis C virus (HCV) infection managed in German office-based practices.Methods: The analysis included HCV genotype 1-infected, treatment-naïve and treatment-experienced patients treated with BOC or TVR. Demographic, treatment history, virological response, safety, and patient management data were collected.Results: Of a total 1087 patients, 58.1 % achieved sustained virological responses (SVR). Response rates were higher in treatment-naïve (BOC 55 %; TVR 63.4 %) and prior relapse patients (BOC 63.2 %; TVR 74.5 %) versus previous null-responders (BOC 14.3 %; TVR 25 %). The most commonly reported adverse event overall was fatigue (60.6 %); 45.8 % patients experienced hemoglobin < 10 g/dL. Patients with cirrhosis had lower rates of SVR versus those without (42.9 % vs. 60.7 %, respectively), and had a higher incidence of serious adverse events (SAEs) (16.7 % vs. 8.6 %, respectively) and treatment discontinuation (44.6 % vs. 25.2 %, respectively). According to recommended response-guided treatment algorithms, about 70 % of patients were managed appropriately, 11/10 % (BOC/TVR) received unnecessarily extended therapy, and 19/7 % (BOC/TVR) received inappropriately shortened therapy.Conclusions: The efficacy and safety of BOC- and TVR-based triple therapy in this large, “real-world” cohort were largely comparable to that reported in pivotal clinical trials, although SVR rates were lower overall. Recommended futility or treatment extension rules were violated in a substantial proportion of patients with potential implications for response, adverse events and costs.
Keywords: Virushepatitis; Hepatitis C; Leber; Telaprevir; Boceprevir; Peginterferon; Kohorte